A brief history of Indonesia : Sultans, spices, and tsunamis : the incredible story of Southeast Asia's largest nation - Hannigan, Tim (Tokyo ; Rutland, Vermont : Tuttle Publishing, 2015)
"Indonesia is the fabled Spice Islands of every school child's dreams--one of the most colorful and fascinating countries in history. These are the islands that Europeans set out on countless voyages to discover and later fought bitterly over in the 15th, 16th and 17th centuries. This was the land that Christopher Columbus sought and Magellan actually reached and explored. One tiny Indonesian island was even exchanged for the island of Manhattan in 1667! This fascinating book tells the story of Indonesia as a narrative of kings, traders, missionaries, soldiers and revolutionaries--featuring stormy sea crossings, fiery volcanoes, and the occasional tiger. It recounts colorful visits by foreign travelers who passed through these shores for centuries--from Chinese Buddhist pilgrims and Dutch adventurers to English sea captains and American movie stars. For readers who want an entertaining introduction to Asia's most colorful country, this is the perfect book"-- |c Provided by publisher.
Point of departure : the archipelago -- From hobbits to Hinduism : prehistory to Indianisation -- Empires of imagination : Hindu-Buddhist Java -- Saints and winners : the arrival of Islam -- Spice invaders : the Europeans arrive -- The clash of civilisations : from company to empire -- Rust en orde : the Dutch East Indies -- Brave new world : the rise of nationalism -- Freedom or death : war and revolution -- Years of living dangerously : the Sukarno era -- A new order : Suharto, crisis, reform -- Epilogue : Indonesia, rising.
Bibliography : pages 280-282.
Keywords: Indonesia -- History